MONITORING DAN EVALUASI PENERAPAN STANDAR NASIONAL INDONESIA BIDANG BAHAN KONSTRUKSI BANGUNAN DAN REKAYASA SIPIL JALAN RAYA - Taufik Mulyono, Agus; Nuraini, Nuraini; Rusmanawati, Dian (Jurnal Transportasi, 2010)
The current performance of the application of quality standards in the administration of road infrastructure is very alarming because the average level of achievements in the field is not greater than 50.0%. The average usage rate of the general Indonesian National Standard (SNI), related to building construction materials, and the specific SNI, related to civil engineering, in road infrastructure contract documents are not more than 30.0%. A logic model of monitoring and evaluation of SNI in the operation of road infrastructure was built in this study with a systemic, hierarchical, and comprehensive approach. The focus of this research is to determine the factors and variables in each subsystem, with monitoring and evaluation of SNI 03-3425-1994 (procedures for the implementation of a thin layer of asphalt concrete for highway) on the maintenance of national roads in Yogyakarta Special Region was selected as a case study. The results showed that the aspect acceptable, applicable, and user friendly are in pretty good category (50.0%-75.0%) but the portable aspect is in the unfavorable category (25.0%-50.0%). This result gives an indication that the socialization activities of SNI, which includes measures to recognize, acquire, and archive need to be improved in all units of stakeholders associated with road handling, including universities, so that in the future it will create communities with standard minded in the field of building construction materials and civil engineering. Also, there is a need to change the shape of SNI books pocket book shape, which makes it easier to take to the field.Keywords: implementation, monitoring, evaluation, Indonesian National Standard